Biodelignifikasi Bunga Jantan Kelapa Sawit Pasca Anthesis Menggunakan Trametes Versicolor - Ratih Rahhutami; Aline Sisi Handini; Indriana Lestari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
The purpose of this study were to determine the effect of biodelignification with Trametes versicolor and to get the best dosage of Trametes versicolor on the levels of lignin, holocellulose, hemicellulose and cellulose of oil palm male flowers post anthesis. This research was conducted at Laboratory of Chemistry Politeknik Kelapa Sawit Citra Widya Edukasi and Laboratory of Biochemistry Institut Pertanian Bogor in April – Oktober 2019. This study used a one factor completely randomized design method with 2 treatments: Trametes versicolor 40 ml (A1) and Trametes versicolor 60 ml (A2). Each treatments were three replications. The total unit of experiments were 6 unit. Data were analized with analysis of variance with α 5 %, if there was a significant treatment effect, the further analysis using LSD (Least Significant Differences). The results showed that biodelignification with Trametes versicolor did not significantly affect for all variabels and the dose of Trametes versicolor showed the same effectiveness for the levels of lignin, holocellulose, hemicellulose, and cellulose of oil palm male flowers post anthesis.